781 IMPROVING THE QUALITY OF DO NOT ATTEMPT CARDIO-PULMONARY RESUSCITATION (DNACPR) FORM COMPLETION. (8th March 2022) - Rasquinha, M; Ng, K; Hillarious, A; Pugh, L; Ghobrial, H; Emuss, D; Shiel, K; Vettasseri, M
Abstract: Introduction: The completion of a Do Not Attempt Cardio-Pulmonary Resuscitation (DNACPR) form represents an important part of patient care. However, this can be a sensitive process that has gained national media interest. The aim of this Quality Improvement (QI) Project was to improve the quality of DNACPR form completion in a Care of the Elderly Department. Methods: The QI project ran from May 2019 to January 2021 and was overseen by a multi-disciplinary team (including patient representation). DNACPR forms on the Care of the Elderly wards were audited monthly against 7 standards which correspond to key sections on the DNACPR form. During the data collection process, interventions were implemented using Plan-Do-Study-Act cycles. Interventions included: appointing 'DNACPR Champions' to complete monthly audits and provide personalised clinician feedback, the introduction of a new mandatory e-learning module, the creation of an alert system on nerve centre (the Trust's electronic handover system) and the development of new DNACPR patient information including webpage development, videos and leaflets. Results: The project has led to sustained improvements in majority of the 7 standards. The biggest improvements were seen in the inclusion of a review date, correct completion of the mental capacity assessment and the use of patient information leaflets. The documentation of discussions with patient and relatives remained below the audit standards and was largely unchanged during the QI project. Conclusion: A multi-disciplinary and multi-faceted QI approach has shown to improve the quality of DNACPR form completion. Further work is needed to continue this process and a focus on staff training and ward-level processes will be the priority.